STUDY TO REDUCE VELOCITY NON-UNIFORMITY IN JAW CRUSHER - Ri, Kwang Myong; Hong, Sok Gun; Ri, Song (Indonesian Journal of Engineering and Science, 2025)
Jaw crushers are widely used in mining and construction for primary rock size reduction, but their conventional designs often exhibit high energy consumption and unstable dynamic behavior due to pulsating crushing loads. This study investigates the dynamic characteristics of a jaw crusher and proposes an improved inertia distribution strategy to enhance load smoothing while reducing flywheel mass. A combined simulation framework integrating the Discrete Element Method (DEM), rigid-body dynamic modeling, and optimization analysis was employed. DEM simulations were used to model ore fragmentation and quantify the cyclic forces acting on the moving jaw, which were found to follow a Gaussian-type distribution with respect to crank phase angle. The resulting load model was incorporated into a dynamic simulation to evaluate angular velocity fluctuations and motor load behavior. The results show that increasing flywheel mass improves rotational stability but increases start-up load. An optimized eccentric mass installed on a low-mass flywheel reduced start-up time by 35% and velocity non-uniformity by 45%, improving crusher dynamic performance.